Vesicular Glutamatergic Transmission in Noise-Induced Loss and Repair of Cochlear Ribbon Synapses - Kyunghee X. Kim; Shelby Payne; Aizhen Yang-Hood; Song-Zhe Li; Bethany Davis; Jason Carlquist; Babak V-Ghaffari; Jay A. Gantz; Dorina Kallogjeri; James A. J. Fitzpatrick; Kevin K. Ohlemiller; Keiko Hirose; et al. (2019)
Noise-induced excitotoxicity is thought to depend on glutamate. However, the excitotoxic mechanisms are unknown, and the necessity of glutamate for synapse loss or regeneration is unclear. Despite absence of glutamatergic transmission from cochlear inner hair cells in mice lacking the vesicular glutamate transporter-3 (Vglut3KO), at 9–11 weeks, approximately half the number of synapses found in Vglut3WT were maintained as postsynaptic AMPA receptors juxtaposed with presynaptic ribbons and voltage-gated calcium channels (CaV1.3). Synapses were larger in Vglut3KO than Vglut3WT. In Vglut3WT and Vglut3+/− mice, 8–16 kHz octave-band noise exposure at 100 dB sound pressure level caused a threshold shift (∼40 dB) and a loss of synapses (>50%) at 24 h after exposure. Hearing threshold and synapse number partially recovered by 2 weeks after exposure as ribbons became larger, whereas recovery was significantly better in Vglut3WT. Noise exposure at 94 dB sound pressure level caused auditory threshold shifts that fully recovered in 2 weeks, whereas suprathreshold hearing recovered faster in Vglut3WT than Vglut3+/−. These results, from mice of both sexes, suggest that spontaneous repair of synapses after noise depends on the level of Vglut3 protein or the level of glutamate release during the recovery period. Noise-induced loss of presynaptic ribbons or postsynaptic AMPA receptors was not observed in Vglut3KO, demonstrating its dependence on vesicular glutamate release. In Vglut3WT and Vglut3+/−, noise exposure caused unpairing of presynaptic ribbons and presynaptic CaV1.3, but not in Vglut3KO where CaV1.3 remained clustered with ribbons at presynaptic active zones. These results suggest that, without glutamate release, noise-induced presynaptic Ca2+ influx was insufficient to disassemble the active zone. However, synapse volume increased by 2 weeks after exposure in Vglut3KO, suggesting glutamate-independent mechanisms. SIGNIFICANCE STATEMENT Hearing depends on glutamatergic transmission mediated by Vglut3, but the role of glutamate in synapse loss and repair is unclear. Here, using mice of both sexes, we show that one copy of the Vglut3 gene is sufficient for noise-induced threshold shift and loss of ribbon synapses, but both copies are required for normal recovery of hearing function and ribbon synapse number. Impairment of the recovery process in mice having only one functional copy suggests that glutamate release may promote synapse regeneration. At least one copy of the Vglut3 gene is necessary for noise-induced synapse loss. Although the excitotoxic mechanism remains unknown, these findings are consistent with the presumption that glutamate is the key mediator of noise-induced synaptopathy.